The Effects of Cryotherapy on Proprioception System. (11th November 2014) - Furmanek, Mariusz Paweł; Słomka, Kajetan; Juras, Grzegorz
Abstract : Proprioception plays an important role in the complex mechanism of joint control. Contemporary sport activities impose extremely high physical demands on athletes. Winter sports are played in areas with excessively low temperatures. Moreover, many athletes are subjected to treatments that involve local lowering of the body temperature before, during, and after physical activity. This work reviews the current knowledge regarding the influence of local cryotherapy on the proprioception system. The reviewed literature identified several tests that evaluate different aspects of proprioception. There is no universally agreed protocol, or clear set of criteria for test conditions. The outcomes of different tests and assessments of cryotherapy procedures using different cold modalities are poorly correlated. In general, the published results on the mechanism of cryotherapy effects on proprioception are not uniquely conclusive and are frequently contradictory. Additional high-quality research is required to explicitly answer the following questions: (1) whether local cryotherapy influences all aspects of proprioception; (2) whether the current methods of evaluation are adequate for the exploration of the relationship between cryotherapy and proprioception; and (3) whether the application of local cryotherapy is safe for athletes regarding proprioception. The review clearly showed that there is no comprehensive model relating cryotherapy and proprioception.